THE ROLE OF ARTIFICIAL INTELLIGENCE IN DIAGNOSTICS: CURRENT APPLICATIONS AND FUTURE PROSPECTS.: JPUMHS;2024:14:03,112-118.http://doi.org/10.46536/jpumhs/2024/14.03.542 - Farzana Mallah1 , Farheen Shaikh2 , Alina Saqib3 , Bashir Ahmed khuhro4 , Sikandar Ali Siyal5 , Nimra ameen6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
Artificial Intelligence AI refers to the simulation of human intelligence processes by machines,especiallycomputersystems.Such processesincludelearning,reasoning,problem solving, perception, and language understanding.